Understanding the Role of Business Analysts in Digital Transformation: A Multivocal Literature Review - Mashhood, A; Senapathi, M (Australasian Conferences on Information Systems (ACIS), 2021)
In recent years, Digital Transformation (DT) has emerged as an important phenomenon in both academic and practitioner literature. Organisations are striving to transform to meet the dynamic needs and expectations of customers as social, mobile, and digital technologies continue to transform people’s lives. While the significance of business analysts in bridging the business/information technology and client-developer gap has been recognised in the industry, there has been limited research into the skills and practices employed by business analysts. In particular, there is lack of empirical research in understanding the relevance and significance of the role of business analysts in DT. This instigated the need for a Multivocal Literature Review (MLR) - we adopted the context, content, process, and outcomes framework to review both peer-reviewed and a selection of grey literature to investigate the skills, practices, and services employed by business analysts in DT. Our findings reveal that business analysts must build a skill set composed of deep business knowledge, collaboration and facilitation skills, agile methods and continuous learning to effectively meet expectations of DT initiatives.
Keywords: Digital Transformation; Business Analyst; Multivocal Literature Review